1994
DOI: 10.1007/bf01103767
|View full text |Cite
|
Sign up to set email alerts
|

Delayed-type hypersensitivity response in an isogenic murine model of paracoccidioidomycosis

Abstract: The specific delayed-type hypersensitivity (DTH) response was evaluated in resistant (A/SN) and susceptible (B10.A) mice intraperitoneally infected with yeasts from a virulent (Pb18) or from a non-virulent (Pb265) Paracoccidioides brasiliensis isolates. Both strains of mice were footpad challenged with homologous antigens. Pb18 infected A/SN mice developed an evident and persistent DTH response late in the course of the disease (90th day on) whereas B10.A animals mounted a discrete and ephemeral DTH response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
28
0
4

Year Published

1995
1995
2013
2013

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 25 publications
5
28
0
4
Order By: Relevance
“…DTH reactions were always evaluated just before sacrifice of the animals used in the CFU assays by the footpad test, under previously determined conditions (17). Briefly, mice were inoculated with 25 l of Fava Netto's antigen (16) and footpad thickness was measured with a caliper (Mitutoyo Corporation, Tokyo, Japan) immediately before and 24 h after antigen inoculation.…”
Section: Methodsmentioning
confidence: 99%
“…DTH reactions were always evaluated just before sacrifice of the animals used in the CFU assays by the footpad test, under previously determined conditions (17). Briefly, mice were inoculated with 25 l of Fava Netto's antigen (16) and footpad thickness was measured with a caliper (Mitutoyo Corporation, Tokyo, Japan) immediately before and 24 h after antigen inoculation.…”
Section: Methodsmentioning
confidence: 99%
“…The DTH reactions were always evaluated just before sacrifice of the same animals used in the CFU assays by the footpad test according to previously determined conditions (19). Briefly, mice were inoculated with 25 l of Fava Netto antigen (18), and the footpad thickness was measured with a caliper (Mitutoyo Corporation, Tokyo, Japan) immediately before and 24 h after antigen inoculation.…”
Section: Animals Breeding Pairs Of Homozygous Il-4-deficient (Il-4mentioning
confidence: 99%
“…We have previously shown that in susceptible (B10.A), but not in resistant (A/Sn), mice, Pb infection is accompanied by suppression of the Ab response to unrelated Ags and an impaired delayedtype hypersensitivity reaction (9,10). In the present work, we selected these two polar mouse strains to ascertain by comparison which of the macrophage-derived products could be associated with resistance or susceptibility to Pb infection.…”
mentioning
confidence: 99%